Kinerja Sektor Publik Pada Masa Pandemi Covid-19 Berdasarkan Teori Isomorfisma Institusional - Dewi, Sukma; Sokarina, Ayudia; Mariadi, Yusli Mariadi (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This study aims to analyze the performance of the Mataram City Personnel and Human Resources Development Agency (BKPSDM) during the COVID-19 pandemic based on the theory of institutional isomorphism. This research is included in the type of qualitative research. The method of data collection is done by using documentation techniques that are equipped with interviews. Data analysis was carried out in two stages, firstly analyzing performance based on the balanced scorecard, secondly elaborating with institutional isomorphism theory. The results of this study indicate that the performance of the Mataram City BKPSDM based on the balanced scorecard measurement is good as the reality that the Mataram City BKPSDM has provided adequate services so that customers feel satisfied. Even the Mataram City BKPSDM routinely provides education and training every year as an effort to improve the professionalism of human resources. Although the reality is different, it is shown by the inadequate facilities and infrastructure of the Mataram City BKPSDM and the percentage of budget realization achieving the criteria of being less efficient. On the other hand, the performance of the Mataram City BKPSDM is not good from the point of view of the institutional isomorphism theory. This is indicated by the dependence of the Mataram City BKPSDM on local and central governments, both in the form of resources, finances, and the reward system, so that there is no other choice but to comply with the rules and demands in order to continue to get the distribution of funds through the budget allocation process from the central government and the government. in order to receive the award